Amnion-derived hydrogels as a versatile platform for regenerative therapy: from lab to market - Kafili, Golara; Niknejad, Hassan; Tamjid, Elnaz; Simchi, Abdolreza (Frontiers in Bioengineering and Biotechnology, 2024)
In recent years, the amnion (AM) has emerged as a versatile tool for stimulating tissue regeneration and has been of immense interest for clinical applications. AM is an abundant and cost-effective tissue source that does not face strict ethical issues for biomedical applications. The outstanding biological attributes of AM, including side-dependent angiogenesis, low immunogenicity, anti-inflammatory, anti-fibrotic, and antibacterial properties facilitate its usage for tissue engineering and regenerative medicine. However, the clinical usage of thin AM sheets is accompanied by some limitations, such as handling without folding or tearing and the necessity for sutures to keep the material over the wound, which requires additional considerations. Therefore, processing the decellularized AM (dAM) tissue into a temperature-sensitive hydrogel has expanded its processability and applicability as an injectable hydrogel for minimally invasive therapies and a source of bioink for the fabrication of biomimetic tissue constructs by recapitulating desired biochemical cues or pre-defined architectural design. This article reviews the multi-functionality of dAM hydrogels for various biomedical applications, including skin repair, heart treatment, cartilage regeneration, endometrium regeneration, vascular graft, dental pulp regeneration, and cell culture/carrier platform. Not only recent and cutting-edge research is reviewed but also available commercial products are introduced and their main features and shortcomings are elaborated. Besides the great potential of AM-derived hydrogels for regenerative therapy, intensive interdisciplinary studies are still required to modify their mechanical and biological properties in order to broaden their therapeutic benefits and biomedical applications. Employing additive manufacturing techniques (e.g. bioprinting), nanotechnology approaches (e.g. inclusion of various bioactive nanoparticles), and biochemical alterations (e.g. modification of dAM matrix with photo-sensitive molecules) are of particular interest. This review article aims to discuss the current function of dAM hydrogels for the repair of target tissues and identifies innovative methods for broadening their potential applications for nanomedicine and healthcare.